2016
DOI: 10.1103/physrevb.93.115302
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopic studies of the electronic structure of chromium-basedp-type transparent conducting oxides

Abstract: The valence band structure of p-type transparent oxides-crystalline Mg x Cr 2−x O 3 and nanocrystalline Cu x CrO y -is analyzed as a function of incoming photon energy. The valence band of both p-type transparent conducting oxides shows striking similarities to measurements on crystalline CuCrO 2 :Mg with all films showing that chromium states compose the top of the valence band, suggesting that the valence-band structure is dominated by the presence of the Cr-O 6 octahedra. A comparison of the valence band be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In the second case, the thermal energy activates the small polarons and σ can be expressed as Equation (3). CuCrO 2 is known as a polaronic material where the transport mechanism is limited by small polaron hopping (SPH) [72,91,92,93,94]. …”
Section: Resultsmentioning
confidence: 99%
“…In the second case, the thermal energy activates the small polarons and σ can be expressed as Equation (3). CuCrO 2 is known as a polaronic material where the transport mechanism is limited by small polaron hopping (SPH) [72,91,92,93,94]. …”
Section: Resultsmentioning
confidence: 99%
“…Mg:Cr2O3 films grown on Al2O3 by the same group showed a small polaron hopping conduction being the limiting factor in the material's conductivity. 168,169 Recently Zhang et al have reported perovskite Sr-doped LaCrO3 (La1-xSrxCrO3) with high figure of merits as new p-type TCOs. 164 The authors have shown that the lowest excitation in LaCrO3 results from a t2g 3 → eg 0 transition is at ≈2.8 eV but formally dipole forbidden.…”
Section: Cr-based Oxides (3d 3 )mentioning
confidence: 99%
“…In 2 O 3 [31], NiO [24,26,32,33], SnO/SnO x [34][35][36][37] and b-Ga 2 O 3 [38][39][40]. (ii) Mixed oxides: In 2 O 3 -Ag 2 O [41,42]; (iii) Chromium based oxides: LaCrO 3 [43], Cr 2 O 3 [44,45]; (iv) Ag-, Cu-, Pd-and Pt-based delafossites [46][47][48][49][50][51][52][53][54][55][56]; (v) Layered oxychalcogenides: LaCuOS [57][58][59] and LaCuOSe [60]; (vi) Spinel oxides: NiCo 2 O 4 [61,62], ZnCo 2 O 4 [63,64], ZnIr 2 O 4 [63] and ZnRh 2 O 4 [65,66], etc. ; (vii) Others: SnSeO [67], Ba 2 BiTaO 6 [68], SrCu 2 O 2 [69][70][71], [Cu 2 S 2 ][Sr 3 Sc 2 O 5 ] [72] or La 2/3 Sr 1/ 3 VO 3 [73].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%